Analisis Indeks Daya Saing dan Pengaruh Sektor Pariwisata dalam Meningkatkan Ekonomi Daerah Kota Batu - Niken Puspitasari; Farida Rahmawati (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2022)
The research of the tourism competitiveness index and multiple linear regression tests are used in Batu City research to improve the economy in the tourism sector. The results i Business Environment, Safety and Security, Health and Hygiene, Human Resources and Labor Market, Price Competitiveness, Environmental Sustainability, and Ground and Port Infrastructure are all in the early stages of development, while the indicators of Health and Hygiene, ICT Readiness, Prioritization of Travel & Tourism, International Openness, and Tourist Service Infrastructure are still in the early stages of development. Tourism sector, which is related to the tourism competitiveness index, has to have a significant and positive effect on local generated revenue, whereas the room occupancy rate and total population have no significant and negative effect.